Size reduction of cellulosic biomass for biofuel manufacturing - Zhang, Meng (Kansas State University, 2013)
Currently, transportation is almost entirely dependent on petroleum-based fuels (e.g. gasoline, diesel fuel, and jet fuel). Increasing demands for sustainable sources of liquid transportation fuels make it imperative to develop alternatives to petroleum-based fuels. Biofuels derived from cellulosic biomass (forest and agricultural residues and dedicated energy crops) have been recognized as promising alternatives to petroleum-based liquid fuels. Cellulosic biofuels not only reduce the nation’s dependence on foreign petroleum but also improve the environment through reduction of greenhouse gas emissions. In order to convert cellulosic biomass into biofuels, cellulosic biomass must go through a size reduction step first, because large size cellulosic biomass (whole stems of herbaceous biomass or chunks of woody biomass) cannot be converted to biofuels efficiently with the current conversion technologies. Native cellulosic biomass has limited accessibility to enzyme due to its structural complexity. Size reduction can reduce particle size and disrupt cellulose crystallinity, rendering the substrate more amenable to enzymatic hydrolysis. The purpose of this research is to provide knowledge of how size reduction alters biomass structural features, and understand the relationships between these biomass structural features and enzymatic hydrolysis sugar yield. This research is also aimed to investigate the impacts of process parameters in biomass size reduction on the conversion of cellulosic biomass to biofuels to help realize cost-effective manufacturing of cellulosic biofuels. This dissertation consists of eleven chapters. Firstly, an introduction of this research is given in Chapter 1. Secondly, Chapters 2 presents a literature review on cellulosic biomass size reduction. Thirdly, a preliminary experimental study is included in Chapter 3. Chapters 4 to 6 present a three-phase study on confounding effects of two important biomass structural features: particle size and biomass crystallinity. Chapters 7 and 8 investigate effects of sieve size used in size reduction of woody and herbaceous biomass, respectively. Chapters 9 and 10 focus on the relationship between particle size and sugar yield. Chapter 11 studies effects of cutting orientation in size reduction of woody biomass. Finally, conclusions and contributions are given in Chapter 12.
Keywords: Cellulosic biofuel; Hydrolysis; Pretreatment; Size reduction; Industrial Engineering (0546)